Body surface area is a potential obesity index: Its genetic determination and its causality for later‐life diseases. Issue 1 (10th December 2022) - Yu, Xing‐Hao; Cao, Rong‐Rong; Yang, Yi‐Qun; Deng, Fei‐Yan; Bo, Lin; Lei, Shu‐Feng
Abstract: Objective: This study aimed to identify novel genetic factors that contribute to body surface area (BSA) and explore its relationship with complex traits and diseases. Methods: Based on more than 330, 000 European individuals in the UK Biobank, the first large‐scale genome‐wide association study for BSA was performed. Comprehensive genetic analysis and enrichment analysis were then performed to explore the biological function of the identified loci. The genetic correlations and causal associations between BSA and other anthropometry parameters, early growth indices, and later‐life diseases, respectively, were assessed by complex genetic approaches. Results: Genome‐wide association study analysis identified a total of 456 conditionally independent single‐nucleotide polymorphism mapping genes with known functions in the regulation of adipogenesis and metabolism and enriched in adipogenesis‐related pathways. BSA was highly genetically correlated with obesity phenotypes, and all the studied anthropometry parameters from the UK Biobank were significantly positively associated with BSA. BSA was phenotypically associated with 13 chronic diseases and genetically associated with 6 diseases. Mendelian randomization analyses showed that BSA has a causal effect in increasing the risk of some diseases. Conclusions: These findings increase understanding of genetic determinants for BSA and its relationship with complex traits and diseases, and BSA could be regarded as a potential obesity trait.